Chief for a Day: Elite Capture and Management Performance in a Field Experiment in Sierra Leone - Voors, Maarten; Turley, Ty; Bulte, Erwin; Kontoleon, Andreas; List, John A. (Management Science, 2018)
We use a field experiment in Sierra Leone to examine how the identity of the manager influences rent seeking and performance in participatory development projects. Specifically, we vary the composition of a committee responsible for implementing a development project—local elites or randomly selected villagers. The design is unique in that it permits us to explore the effectiveness of two alternative local governance modalities and the extent of elite capture in community projects. We find little evidence that local elites capture project resources. We do observe they are better managers of development projects. Improved performance covaries with a proxy for power of the local chief. Data and the online appendix are available at https://doi.org/10.1287/mnsc.2017.2866 . This paper was accepted by Teck-Hua Ho, behavioral economics.